Effect of oat flour on sensory and physico-chemical properties of chicken meatball - Hossan, MI; Biplob, MAKA; Khan, MRI; Rahman, MM (Meat Research, 2024)
This study evaluated the effect of oats (0%, 5%, 10%, and 15%) on chicken meatball quality. The samples were stored at 4˚C for 12 days and analyzed on days 0, 4, 8, and 12. Sensory attributes (color, flavor, tenderness, juiciness, overall acceptability), physicochemical properties (proximate components, pH, cooking loss), and microbiological quality (TVC, TCC, TYMC) were assessed. Results showed that oats increased cooking yield by reducing weight loss from 26.95% to 27.76%. The 5% oats group had the most preferred color, odor, tenderness, and juiciness. The least preferred color was found in the control group. Flavor scores ranged from 3.91 to 4.8, with no significant differences, but the most preferred flavor was observed in the 10% oats group. Tenderness was highest in the 10% oats group, with scores ranging from 3.41 to 4.33. Juiciness scores ranged from 3.33 to 4.33, with no significant differences; the 5% oats group had the highest juiciness. Overall acceptability scores ranged from 3.50 to 4.16, with the highest score recorded in the 5% oats group. Dry matter content ranged from 47.05% to 50.67%, with the 5% oats group exhibiting the most preferable content. Crude protein content ranged from 19.97% to 21.71%, with significant differences observed between the control and 10% oats groups. Ether extract content ranged from 7.82% to 8.3%, with the 15% oats group having the lowest ether extract content. Ash content ranged from 1.19% to 1.35%, with significant differences across treatments. pH values of raw meatballs ranged from 5.55 to 5.69, with the 5% oats group showing the most preferable pH. Cooking loss ranged from 26.68% to 28.41%, with the most preferable cooking loss observed in the 15% oats group. TBA values ranged from 0.09 to 0.15, with no significant differences observed across treatments. Microbial counts (TVC, TCC, and TYMC) increased with storage time, with the control group showing the highest counts.